Feral Thinking: Religion, Environmental Education, and Rewilding the Humanities - Mayse, Ariel Evan (Religions, 2024)
The contemporary American university largely operates as an agent of domestication, tasked more with enforcing the social and economic order than with expanding the horizons of possibility. The dawn of the Anthropocene, however, demands that we reconceive of the humanities not as self-sufficient, hierarchical, or divided away from other modes of seeking knowledge but as core to what human being and responsibility ought to mean in the more-than-human world. The present essay makes a case for reworking—and rethinking—the American university along the lines of Mark C. Taylor’s prompt to reconceive of the academy as a multidisciplinary forum for the “comparative analysis of common problems”. I suggest that religious teachings—and religious traditions themselves—can offer models for the intertwining of the humanities (literature, poetry, philosophy, the expressive and applied arts), the social sciences (the study of governance, political thought, the study and formulation of law), and the natural sciences as well as mathematics and engineering. Further, I argue that when faced with radical and unprecedented changes in technological, social, economic, and environmental structures, we must, I believe, engage with these traditional texts in order to enrich and critique the liberal mindset that has neither the values nor the vocabulary to deal with the climate crisis. We must begin to sow new and expansive ways of thinking, and I am calling this work the “rewilding” of our universities. Parallel to the three Cs of rewilding as a conservation paradigm, I suggest the following three core principles for the rewilding of higher education: creativity, curriculum, and collaboration. Though I focus on the interface of religion, ecology, and the study of the environmental, social, and moral challenges of climate change, I suggest that these categories of activity should impact all domains of inquiry to which a university is home.